Entrepreneurs' Perception Toward International Cooperation and Government Programs Concerning Entrepreneurship - Saucedo-Bendek, Omaira; Ewel, Sebastián; Roman-Roig, Francisco Javier (Frontiers in Education, 2020)
Globally, and regionally, countries are implementing programs and policies to foster entrepreneurship. The most successful programs have aligned efforts by various stakeholders to thrive. This document contrasts the needs of early-stage and aspiring entrepreneurs in Bolivia and their perceptions on the current programs they have attended. The authors use Elma Van de Mortel's model to describe the stages the entrepreneurship undergoes, interpreting Bolivia is in the first of the three stages. Start-Up Chile is used as a benchmark program toward a more sophisticated entrepreneurship structure, to conclude efforts should be made to align stakeholders including the government, financial services, incubators, accelerators, universities, and others.